KARAKTERISTIK KIMIA DAN FISIK FETUCINI DENGAN VARIASI PERBANDINGAN TEPUNG TERIGU DAN TEPUNG PORANG (Amorphophallus muelleri) - Asti Mayada; Mardiana; Tubagus, Robi (Pasundan Food Technology Journal (PFTJ), 2025)
Wheat grains, as the main ingredient of wheat flour, have experienced an increase in imports, so alternatives are needed to address this issue. The use of porang flour, which is rich in glucomannan, in the production of fettuccine can reduce the use of wheat flour and improve physical and chemical characteristics. This study aims to determine the effects and identify the best formulation based on variations in the ratio of wheat flour to porang flour in fettuccine on its chemical and physical characteristics. This research was conducted experimentally using a completely randomized design with one factor and four treatment variations: P1 (80% wheat flour: 20% porang flour), P2 (70% wheat flour: 30% porang flour), P3 (60% wheat flour: 40% porang flour), P4 (50% wheat flour: 50% porang flour), with each treatment repeated three times. The analytical parameters used in this study included chemical analysis, moisture content, ash content, protein, fat, carbohydrates, and oxalic content, as well as physical analysis, namely cooking loss, and elasticity. The results showed that variations in the ratio of wheat flour to porang flour had a significant effect on chemical parameters (moisture content, ash content, protein, fat, oxalic acid) and physical parameters (cooking loss, elasticity), but did not have a significant effect on carbohydrate content. Treatment P1 (80% wheat flour: 20% porang flour) produced the best fettuccine, including a moisture content of 8.06% db, ash content 4.37% db, protein 9.11% db, fat 2.20% db, carbohydrate 85.34% db, oxalic content 8.31 mg/100g, cooking loss 6.09%, and elasticity 13.32%.